KEPEMIMPINAN KONTEKSTUAL KEPALA MADRASAH IBTIDAIYAH DAN SD ISLAM DI KOTA SALATIGA, JAWA TENGAH - Rahmat Hariyadi (MIYAH : Jurnal Studi Islam, 2023)
This paper aims to describe the contextual leadership of the Principals of Madrasah Ibtidaiyah (MI), and Islamic Elementary School which includes (1) Their understanding of the internal and external environment (2) Their understanding of the various strengths that exist in stakeholders, and the ability to capitalize on them for the success of their schools; (3) Their understanding of society's expectations, as well as their response to these expectations; and (4) Efforts by school principals to encourage high performance and innovation in teachers and school staff. This paper is based on the results of a qualitative descriptive study conducted at three schools: State Madrasah Ibtidaiyah, Private Madrasah Ibtidaiyah and Islamic Elementary School in Salatiga. Data were collected using multiple sources, including participant observation, interviews with a variety of people including the principal, other school leaders, teachers, school council/board members, parents and students, and documents study. Data analysis is done through: (1) data collection, (2) data reduction, (3) data display (data display), and (4) conclusion and verification. The result of study shows that (1) school principals have a good understanding of the internal and external conditions of the school they lead, (2) school principals can find the strengths that exist in stakeholders and are able to capitalize on them for school progress, (3) school principals absorb aspirations and com-munity expectations and trying to provide a satisfactory response, and (4) school principals encourage the perfor-mance of teachers by prioritizing a sense of responsibility and challenges to meet community expectations.